Mothers' perspectives on the lived experience of children with intellectual disability and challenging behaviour. (June 2019) - Kiernan, Joann; Mitchell, Duncan; Stansfield, Jois; Taylor, Carol
Children with intellectual disability and behavioural needs (challenging behaviour) are vulnerable to exclusion from services and communities. The situation is exacerbated by difficulties in accessing appropriate support and services to effectively meet the needs of children and carers. Family perspectives on the 'lived experience' of children can provide insight into how behavioural needs can affect their ability to access everyday experiences. Semi-structured interviews were conducted with mothers of children with intellectual disabilities and challenging behaviours. Phenomenological thematic analysis provided four key themes: finding our way; square services, round needs; behaviour touches everything and belonging. Experience of inclusion and exclusion was a central tenet of the lived experience. Recommendations call for timely proactive and bespoke interventions to identify and support children at risk of exclusion from communities. Early intervention and effective local provision will avoid increased burdens placed on families and services, in supporting children whose needs are currently unmet within child-centred provision.